2015
DOI: 10.1016/j.jpeds.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Age at Weaning and Infant Growth: Primary Analysis and Systematic Review

Abstract: ObjectiveTo test whether earlier age at weaning (age 3-6 months) may promote faster growth during infancy.Study designWeaning at age 3.0-7.0 months was reported by 571 mothers of term singletons in a prospective birth cohort study conducted in Cambridge, UK. Infant weight and length were measured at birth and at age 3 months and 12 months. Anthropometric values were transformed into age- and sex-adjusted z-scores. Three linear regression models were performed, including adjustment for confounders in a stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…It was not possible to explain this difference by environmental, maternal, or infant characteristics; and we therefore tested the possibility of reverse causality. The method proposed by Vail et al (26) was applied, including infants who were still EBF at 3 mo of age, testing whether their mean weight, length, and z score changes between 2 wk and 3 mo of age were associated with subsequent age of discontinuation of EBF. The same analysis was conducted in infants who were still EBF at 4 mo of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not possible to explain this difference by environmental, maternal, or infant characteristics; and we therefore tested the possibility of reverse causality. The method proposed by Vail et al (26) was applied, including infants who were still EBF at 3 mo of age, testing whether their mean weight, length, and z score changes between 2 wk and 3 mo of age were associated with subsequent age of discontinuation of EBF. The same analysis was conducted in infants who were still EBF at 4 mo of age.…”
Section: Resultsmentioning
confidence: 99%
“…Second, this observation could reflect reverse causality, with mothers in this community choosing to continue EBF if their infant was growing well. Research from the United Kingdom has shown that rapid weight gain between birth and 3 mo of age predicted subsequent earlier age of weaning (26). Kramer et al (27) found contrary results: a low WAZ (<−1) at 1 mo increased the risk of both weaning and discontinuation of EBF by 2 mo of age in a Belarusian population.…”
Section: Discussionmentioning
confidence: 99%
“…Later solids introduction doubled the odds of resolution (OR 2.29, CI 1.08 to 4.88, p=0.03). In addition, because larger infants start solids earlier,24 we further adjusted for birth weight (OR 2.13, CI 0.91 to 4.99, p=0.08).…”
Section: Resultsmentioning
confidence: 99%
“…However, the improved efficiency in drinking developed over infancy [23] is retained through weaning. In many mammalian species, including pigs and humans, a period of overlap exists between the onset of solid food intake and the cessation of maternal milk consumption [24][25][26]. Maintaining efficient aerodigestive function in liquid consumption developed through infancy allows the weanling to extract maximum nutrition from increasingly infrequent milk feeds while it navigates the challenges of eating solid food.…”
Section: (A) Implications For Maturation and Response To Behavioural mentioning
confidence: 99%